Development and validation of HPLC method for determination of β-ecdysone from Callisia fragrans (Lindl.) woodson - Vinh, Bui The; Xuan, Phan Nguyen Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
The HPLC method for the determination of β-ecdysone from Callisia fragrans was developed and validated. Thereby, crushed herbal powder of stem and leafs of Callisia fragrans (Lindl.) Woodson was extracted with MeOH by sonification. The MeOH extract was evaporated at low pressure to obtain the residue of total extract. This MeOH fraction was carried out liquid - liquid extracting method with solvents of increasing polarity: n-hexane, EtOAc. The fraction EtOAc containing β-ecdysone was performed by using the HPLC method. The simple chromatographic separation condition was carried out on a C18 column using isocratic mobile phase consisting of 60% (v/v) methanol and 40% (v/v) water with flow rate of 1.0 mL/min. The eluted process was monitored by a diode-array detector at wavelength of 242 nm. Results obtained in validation demonstrated an linear relationship between the corresponding peak areas and the concentration of β-ecdysone: y = 164896x - 42687, as confirmed by the correlation coefficient of 0,998. The concentration of β-ecdysone in Callisia fragrans (Lindl.) Woodson was determined by using the HPLC with 0.052% of dry powder.